2018
DOI: 10.1038/s41598-018-26118-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein profiling as a potential multi-marker approach for obese patients with heart failure: A retrospective study

Abstract: Identification of novel circulating biomarkers predicting death and major cardio-metabolic events in obese patients with heart failure (HF) remains a research priority. In this study, we compared multi-marker profile of non-obese (NOB) and obese (OB) HF patients in relation to mortality outcome. The new multiplex proximity extension assay technology was used to analyze the levels of 92 proteins in plasma samples from HF patients according to body mass index (BMI) categories. At 2-year follow-up, all-cause mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…The notion of MMP1/PAR1 axis was initially demonstrated in the process of infection [ 41 ]. Later, emerging evidence indicated that MMP1/PAR1 axis participated in the pathogenesis of thrombosis [ 42 ], atherosclerosis [ 43 ], and serious cardiac events [ 44 ]. Recent studies support a critical role of MMP1/PAR1 axis in tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of MMP1/PAR1 axis was initially demonstrated in the process of infection [ 41 ]. Later, emerging evidence indicated that MMP1/PAR1 axis participated in the pathogenesis of thrombosis [ 42 ], atherosclerosis [ 43 ], and serious cardiac events [ 44 ]. Recent studies support a critical role of MMP1/PAR1 axis in tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The association between MMP9 and worsening events in chronic HF patients has been described 35 , but there are only few papers about the 2 MMPs identified here. A recent study has shown that MMP1 with protease-activated receptors (PAR) 1 and BNP and NTproBNP were downregulated in obese HF patients 36 . Interestingly, mechanistic research showed that inflammation mediated by MMP1-PAR1 might amplify tumour necrosis factor α signalling in endothelial cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…113 In patients with heart failure, obesity is associated with increased leptin plasma level, whereas the VEGF A plasma level is decreased. 114 Overweight patients with CAD have higher leptin and VEGF blood concentration than overweight controls without CAD, and atorvastatin treatment decreases both leptin and VEGF serum level in CAD subjects. 115 In older adults with MS, leptin and VEGF levels are higher both in serum and in breath condensate than in subjects without MS. 116 Patients with obstructive sleep apnea (OSA) and MS; without OSA but with MS; and without OSA and without MS matched for gender, age, and central obesity have similar leptin and VEGF, serum levels.…”
Section: Human Studiesmentioning
confidence: 95%